Set in stone? : war memorialisation as a long-term and continuing process in the UK, France and the USA - Login, Emma, (Archaeopress, 2016)
Moving beyond the social-political circumstances of a memorial's construction, this study examines memorialisation as a continuing and transformative process. It explores the many ways in which war memorials are repeatedly appropriated, and re-appropriated, undergoing both physical and symbolic transformations.